Slade House [large type] - Mitchell, David (David Stephen) (Thorndike Press large print basic, 2015)
Down the road from a working-class British pub, along the brick wall of a narrow alley, if the conditions are exactly right, you'll find the entrance to Slade House. A stranger will greet you by name and invite you inside. At first, you won't want to leave. Later, you'll find that you can't. Every nine years, the house's residents -- an odd brother and sister -- extend a unique invitation to someone who's different or lonely: a precocious teenager, a recently divorced policeman, a shy college student. But what really goes on inside Slade House? For those who find out, it's already too late.